How to Improve the Self-Esteem of Minangkabau Teenagers Through Agentic Group Guidance? - Indah Wijayanti; Herman Nirwana; Rezki Hariko; Yeni Karneli; Hanifah Usman (Universitas PGRI Yogyakarta, 2026)
Self-esteem is now a global psychological issue that influences mental well-being, achievement, and social relationships. However, research linking self-esteem development to a culture-based counseling approach remains limited, especially in the Minangkabau context, which is rich in values of togetherness and independence. This type of research is a quantitative quasi-experimental method with a non-equivalent design. The subjects of this study were 20 students of Batipuh 1 State Senior High School. The research instrument was a self-esteem checklist developed using a Likert scale. Data were analyzed using the N-Gain test, the Wilcoxon test, and the Mann-Whitney test . The results showed that the Agentic group guidance service in the experimental group was